2012
DOI: 10.1158/1535-7163.mct-11-0289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Docetaxel Resistance Genes in Castration-Resistant Prostate Cancer

Abstract: Docetaxel-based chemotherapy is the standard first-line therapy in metastatic castration-resistant prostate cancer (CRPC). However, most patients eventually develop resistance to this treatment. In this study, we aimed to identify key molecular genes and networks associated with docetaxel resistance in two models of docetaxelresistant CRPC cell lines and to test for the most differentially expressed genes in tumor samples from patients with CRPC. DU-145 and PC-3 cells were converted to docetaxel-resistant cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 43 publications
3
83
1
Order By: Relevance
“…So far, IFIH1 expression has been described mainly as a cytosolic receptor responsible for double-strand RNA recognition and antiviral response (29,30). Marín-Aguilera et al reported on decreased expression of IFIH1 gene in castration-resistant prostate cancers resistant to Docetaxel (DOC) and in prostate cancer cell lines resistant to DOC (42). In contrast, we observed an up-regulation of this gene in TOP-resistant ovarian cancer cell lines.…”
Section: Discussioncontrasting
confidence: 56%
“…So far, IFIH1 expression has been described mainly as a cytosolic receptor responsible for double-strand RNA recognition and antiviral response (29,30). Marín-Aguilera et al reported on decreased expression of IFIH1 gene in castration-resistant prostate cancers resistant to Docetaxel (DOC) and in prostate cancer cell lines resistant to DOC (42). In contrast, we observed an up-regulation of this gene in TOP-resistant ovarian cancer cell lines.…”
Section: Discussioncontrasting
confidence: 56%
“…In previous work, we identified 243 genes with differential expression in CRPC docetaxel-sensitive versus docetaxel-resistant cell lines (16). In the present study, 73 genes from that study together with 20 genes from the literature were tested in tumor specimens of patients with high-risk localized prostate cancer included in a clinical trial of neoadjuvant hormone chemotherapy (17), and compared with nontreated specimens with similar clinical characteristics.…”
Section: Introductionmentioning
confidence: 94%
“…A set of 73 target genes was selected for their relative expression in docetaxel-resistant cells (DU-145R and PC-3R) versus parental cells (DU-145 and PC-3; ref. 16) using DAVID (21) and Ingenuity Pathway Analysis software (http://www.ingenuity.com). Twenty genes highlighted in the literature as potential targets of docetaxel resistance were also selected.…”
Section: Gene Selectionmentioning
confidence: 99%
“…By inducing docetaxel-resistant DU-145 PC cells in culture, Marín-Aguilera compared global gene expression between docetaxel-sensitive and docetaxelresistant cell lines and found that exposing parental cells to TGF-b1 increased their survival in the presence of docetaxel. The result suggested a role of the TGF-b superfamily in conferring docetaxel resistance (Marín-Aguilera et al 2012). It was also reported that men with prostate cancer carrying two copies of the CYP1B1*3 polymorphic variant had a poor prognosis after docetaxel-based therapies compared with others carrying at least one copy of the CYP1B1*1 allele (Sissung et al 2008).…”
Section: Potential Predictive Biomarkers Of Response To Chemotherapymentioning
confidence: 87%